1967
DOI: 10.1001/archneur.1967.00470220021003
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis

Abstract: This chapter was originally intended to cover both amyotrophic lateral sclerosis (ALS) and multiple sclerosis, but we will concentrate on ALS. There are nonetheless several reports from the literature that ionotropic glutamate receptor antagonists have beneficial effects in animal models of multiple sclerosis (1,7,14,58,71,109) and this could develop into a very promising therapeutic area in the future. The interested reader is referred to the following review (59). However, the evidence for involvement of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
3

Year Published

1971
1971
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 13 publications
(2 reference statements)
3
50
0
3
Order By: Relevance
“…In Amyotrophic Lateral Sclerosis they precipitate in cell bodies or the proximal part of axons from motor neurons (Hirano, 1991;Corbo and Hays, 1992). They accumulate in Lewy bodies of Parkinson's disease (Hill et al, 1993), in Neurofibrillary Tangles of Alzheimer's disease (Leigh et al, 1989), and following intoxication by aluminium, hexanedione, acrylamide or β,β′-Iminodipropionitrile (IDPN) (Eyer et al, 1989;Leterrier et al, 1992).…”
mentioning
confidence: 99%
“…In Amyotrophic Lateral Sclerosis they precipitate in cell bodies or the proximal part of axons from motor neurons (Hirano, 1991;Corbo and Hays, 1992). They accumulate in Lewy bodies of Parkinson's disease (Hill et al, 1993), in Neurofibrillary Tangles of Alzheimer's disease (Leigh et al, 1989), and following intoxication by aluminium, hexanedione, acrylamide or β,β′-Iminodipropionitrile (IDPN) (Eyer et al, 1989;Leterrier et al, 1992).…”
mentioning
confidence: 99%
“…In addition, tau and NF-H/NF-M side-arms are abnormally phosphorylated on some of these putative cdk-5-targeted residues in certain neurodegenerative diseases. Hyperphosphorylated tau is the major component of paired helical filaments in Alzheimer' s disease (for reviews, see Goedert, 1993;Lee, 1995), and accumulations of neurofilaments containing heavily phosphorylated NF-H/NF-M side-arms as detected by phosphorylation-dependent antibodies are observed in perikarya and proximal axons in motor neurone disease and in Lewy body pathologies (see Hirano, 1991;336 S. GUIDATO ET AL. Pollanen et al, 1993;Trojanowski et al, 1993;Xu et al, 1993).…”
mentioning
confidence: 99%
“…Because Cdk5 has been shown to phosphorylate some of these in vivo phosphorylation sites of NF (Hellmich et al, 1992;Lew et al, 1992b;Shetty et al, 1993;Sun et al, 1996), it may play important roles in the regulation of cytoskeletal dynamics in neurons under both physiological and pathological conditions. It is known that an altered phosphorylation state of NF is implicated in human neurodegenerative diseases, including Alzheimer disease, Lewy body disease, and motor neuron disease (Hirano, 1991;Trojanowski et al, 1993). Moreover, recent studies using transfection methods and transgenic mice have demonstrated the importance of Cdk5 in neurite outgrowth and neuronal differentiation (Nikolic et al, 1996;Ohshima et al, 1996).…”
mentioning
confidence: 99%